Effects of the Occupational Physical Environmental Conditions and the Individual Characteristics of the Workers on Occupational Stress and Fatigue - Birowo Herusasongko; Adi Heru Husodo; H A Sudibyakto (International Journal of Public Health Science (IJPHS), 2012)
This research was conducted to study the effects of environmental factors i.e. heat stress, thermal comfort, and occupational noise and individual factors of the workers i.e. age, work duration (expressed in months), and nutrition status on occupational fatigue and stress. Occupational fatigue was measured using Reaction Timer L-77 Lakassidaya. Occupational stress was measured using questionnaire adapted from Wambrauw (2010). Heat stress and thermal comfort were measured using Questemp 34 Thermal Environment Meter and Lutron AM-4200 Anemometer. Occupational noise level was measured using Lutron SL-4022 Sound Level Meter. Nutrition status was measured using microtoise and body weight scale. Age and work duration was obtained using a personal profile form filled in by each worker. This research employed Structural Equation Modelling (SEM) consisted of direct and indirect effects of exogenous and endogenous variables on endogenous variables. Data analysis was conducted using AMOS 19 software. Data analysis showed that (1) different level of fatigue was indicated on workers working in different work shifts, (2) there was no direct effects of heat stress and  thermal comfort on occupational fatigue, (3) there was a positive direct effect of occupational noise on workers stress but there was no indication that the stress itself has a direct effect on occupational fatigue, thus preventing the indirect effect of occupational noise on occupational fatigue, (4) there was no direct effect of the age of the workers on occupational fatigue, (5) there was a positive direct effect of the workers age on work duration, but the work duration itself did not exhibit any effect on occupational fatigue so therefore no indirect effect of workers age on occupational fatigue was found in this research, (6) and finally, there was a positive direct effect of nutrition status on occupational fatigue.DOI: http://dx.doi.org/10.11591/ijphs.v1i2.1251